Between Law and Faith: Judicial Dilemmas of Unregistered Polygamy and Divorce in Indonesia - Holilur Rohman; Rishat Ameer Ğafurof; Arif Jamaluddin; Wardah Toyyibah; Abdul Wahab Naf'an (Indonesian Journal of Islamic Law, 2025)
Divorce in unregistered polygamous marriages constitutes one of the most pressing socio-legal challenges in contemporary Indonesia, particularly after the enactment of Supreme Court Circular (SEMA) No. 3 of 2018, which prohibits religious courts from granting isbat nikah for such unions. This article examines two interrelated questions: first, the practical problems of divorce faced by women in unregistered polygamous marriages within the SaMaRa Centre community; and second, the perspectives of religious court judges regarding these issues, assessed through the normative lenses of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) and Maqāṣid al-Sharīʿah. Methodologically, this study adopts qualitative fieldwork, combining semi-structured interviews with women affected by such marriages and judges from religious courts in Surabaya and Probolinggo. The findings reveal divergent judicial approaches: some judges uphold strict procedural consistency in line with SEMA No. 3/2018, while others emphasise fairness and maṣlaḥah (public welfare) to justify more flexible rulings. This divergence underscores a judicial dilemma between procedural uniformity and the imperative of justice for vulnerable women. By situating these debates within international human rights norms and Islamic legal theory, the study emphasises the need to develop a more inclusive legal framework that balances state regulations with gender justice. Ultimately, it argues for stronger judicial pathways to protect women’s rights in informal unions, offering insights into the intersection of law, religion, and social realities in Muslim-majority contexts.